i wanted to burn the language i had been taught : burning language with pedro lemebel (Palíndromo, 2025)
this visual essay presents developments derived from pedro lemebel’s final performance, abecedário (2014), in which the letters from a to z were drawn in neoprene on the pedestrian bridge leading to santiago’s metropolitan cemetery. pedro descends the ramp in a funeral procession, guided by a fiery desire to transform through destruction. he conducts a rite of passage; he sets the abecedário on fire. the alphabetic body is purified by the transformative flame; the language is veiled and rekindled in the embers of conversion. the letters leap from the ground, come alive in blazing flames; the language combusts until disappearance. guided by pedro’s action, i created the abecedário font (2025), based on frames from his performance. the font was constructed through the vectorization of images of the burning letters. it contains only the alphabetic set displayed in the performance, including the letter ñ — a character of the spanish variant of the latin alphabet. to compose the font, glyphs for diacritics were also created, drawn from fragments of the flaming letters. writings composed with abecedário are flammable: pyromaniac texts, manifestos of combustion, embered declarations that warm up and transform. this essay also includes a letter written to pedro and photographic records of the performance vai pegar fogo (2025), performed by myself, in which i set fire to a poster printed with the abecedário font, on the ramp crossing the main access avenue to ilha do desterro (florianópolis, brazil).
Keywords: performance; language; tipography